Effect of vacuum sealing on corrosion resistance of high-velocity arc sprayed coating. Issue 1 (1st January 2023) - Deng, Chunyin; Lu, Zhuang; Lu, Haifeng; Liu, Chenwei; Wu, Shuhui; Qin, Enwei
Abstract: Thermal spray coatings commonly have pores and micro cracks in their structure. Corrosive medium will pass through pores and micro cracks in corrosive conditions and damage the substrate, leading to coating failure and reduced service life. In this study, vacuum impregnation sealing (VIS) and conventional impregnation sealing (CIS) were used to seal high-velocity arc-sprayed NiCr-based coatings. The cross-sectional microstructure of the coating and its porosity are observed by optical microscopy. Energy spectrometry and scanning electron microscopy were used to measure the sealant's penetration depth. corrosion behavior was studied by neutral salt spray testing and electrochemical methods. The results showed that the average depth of sealant penetration by VIS is 275 m, almost three times greater than that of CIS. Better corrosion resistance was indicated in the coating sealed by VIS, which had a smaller corrosion current density and a more noticeable passivation zone than the coating sealed by CIS. The coating sealed by VIS showed no rust stains after 432 hours in the salt spray corrosion environment, but the coating sealed by CIS showed corrosion rust spots after 96 hours. The coating sealed by VIS appeared to have greater corrosion resistance, providing experimental support for its use in engineering.